Cyberpornography - Graham, Roderick (Cybercrime and digital deviance, 2024)
This chapter introduces the reader to cyberpornography and several topics embedded within the category: Sexual deviance in online spaces, pornography consumption, revenge porn, sexting, and sex work. The contrast between the terms indecency and obscenity is also explored, along with the challenges of legislating content along these standards and the controversial concept of “victimless crimes” within this space. The chapter highlights the fine thread along which harm in cyberpornography is defined, noting that even activities in this category deemed victimless or harmless initially may still perpetuate harm due to the ancillary outcomes of cyberpornography (e.g., perpetuation of rape myths, objectification of women).